2-Hydroxy-1-naphthaldehyde-P-hydroxybenzoichydrazone: A New Chromogenic Reagent for the Determination of Thorium(IV) and Uranium(VI) - V. S. Anasuya Devi; V. Krishna Reddy (Journal of Chemistry)
Simple, sensitive, selective, direct, derivative, and simultaneous spectrophotometric methods are developed for the determination of uranium and thorium individually and simultaneously. The methods are based on the reaction of 2-hydroxy-1-naphthaldehyde-p-hydroxybenzoichydrazone (HNAHBH) with thorium(IV) and uranium(VI). HNAHBH reacts with thorium and uranium at pH 6.0 forming stable yellow and reddish brown coloured complexes, respectively. [Th(IV)-HNAHBH] complex shows maximum absorbance at 415 nm. Beer’s law is obeyed over the concentration range 0.464–6.961 μg mL−1 with a detection limit of 0.01 μg mL−1 and molar absorptivity, ε, 3.5 × 104 L mol−1 cm−1. Maximum absorbance shown by [U(VI)-HNAHBH] complex is at 410 nm with Beer’s law range 0.476–7.140 μg mL−1, detection limit 0.139 μg mL−1 and molar absorptivity, ε, 1.78 × 104 L mol−1 cm−1. Highly sensitive and selective second-order derivative methods are reported for the direct and simultaneous determination of Th(IV) and U(VI) using HNAHBH. The applicability of the developed methods is tested by analyzing water, ore, fertilizer, and gas mantle samples for thorium and uranium content.